2016
DOI: 10.1002/ep.12316
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution driving factors analysis: Evidence from economically developed area in China

Abstract: Rapid economic growth is usually accompanied by rising air pollution in China, especially in the economically developed regions. Beijing is the capital of China, which is selected as a study case in this article. The aim of this study is to authenticate if the Environmental Kuznets curve (EKC) hypothesis exists between air pollution and economic growth in Beijing over the period of 1990–2013, and to understand the driving factors of the air pollution by utilizing the Stochastic Impacts by Regression on Populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Ridge regression was employed in this article to examine the impact factors of net CO 2 emissions, and the formal formulation of ridge regression is regarded as one of least squares subject to specific parameters . Linear least square fit is known as a standard method to solve the system of linear equations: Y=Xβ and it seeks to minimize the residual: ||YXβ||2 where Y represents m × 1 vector; X represents m × n matrix ( m ≥ n ); β represents n × 1 vector; ‖‖||| || refers to Euclidean norm.…”
Section: Study Area and Methodologymentioning
confidence: 99%
“…Ridge regression was employed in this article to examine the impact factors of net CO 2 emissions, and the formal formulation of ridge regression is regarded as one of least squares subject to specific parameters . Linear least square fit is known as a standard method to solve the system of linear equations: Y=Xβ and it seeks to minimize the residual: ||YXβ||2 where Y represents m × 1 vector; X represents m × n matrix ( m ≥ n ); β represents n × 1 vector; ‖‖||| || refers to Euclidean norm.…”
Section: Study Area and Methodologymentioning
confidence: 99%
“…Guan et al found that population density was significantly related to smoke and dust in East China, India, North America and North Africa [4]. Li and Sun used a STIRPAT model to study the atmospheric pollution situation in Beijing from 1990 to 2013, and through empirical analysis they found that social and economic factors such as population, urbanization and industry structure have an impact on atmospheric pollutants [5]. Yang et al studied the impact of energy consumption, energy structure, and treatment technology on SO 2 based on the LMDI decomposition method [6].…”
Section: Air Pollution and Its Influencing Factorsmentioning
confidence: 99%
“…For instance, Wang et al applied ridge regression to eliminate multicollinearity for revealing the influence mechanism of socio-economic factors on energy-related carbon dioxide emissions in Guangdong Province, China [65]. Li et al utilized ridge regression to avoid the multicollinearity of independent variables for understanding the driving factors of the air pollution (SO 2 , CO 2 ) in Beijing, China [66].…”
Section: Ridge Regressionmentioning
confidence: 99%